PRESCRIPTION: THE PRESENT INTERPRETATION OF EXTINCTIVE PRESCRIPTION AND THE ACQUISITION OF REAL RIGHTS (The Pretoria Student Law Review, 2021)
The Prescription Act provides that a debt can prescribe or rather ‘expire’ and further that one can acquire ownership through prescription.1 Prescription in simple terms refers to old debt which occurs when it is no longer an obligation for a debtor to pay off their debt. One of the original methods of acquiring real rights is by the passage of time, and other various types of obligations may be rendered unenforceable by the effluxion of time.
Keywords: Prescription Act; debt; acquire ownership; real rights